2017
DOI: 10.1007/s40273-016-0485-x
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Issues Surrounding the Use of Baseline Health-Related Quality of Life Data to Inform Trial-Based Economic Evaluations of Interventions Within Emergency and Critical Care Settings: A Systematic Literature Review

Abstract: warwick.ac.uk/lib-publicationsOriginal citation: Dritsaki, Melina, Achana, Felix A., Mason, James and Petrou, Stavros. (2017) Methodological issues surrounding the use of baseline health-related quality of life data to inform trial-based economic evaluations of interventions within emergency and critical care settings : a systematic literature review. PharmacoEconomics. Permanent WRAP URL:http://wrap.warwick.ac.uk/85039 Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes this work by research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 43 publications
(68 reference statements)
1
25
0
2
Order By: Relevance
“…First, we assumed that the baseline utility value for each patient was − 0.402, the value assigned by the UK EQ-5D-3L tariff to an unconscious health state. This assumption is in keeping with broader methodological practice for trial-based economic evaluations conducted in critical care settings [38]. Moreover, we recently demonstrated that applying alternative fixed baseline utility scores generally had no effect on incremental QALY calculations [38].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…First, we assumed that the baseline utility value for each patient was − 0.402, the value assigned by the UK EQ-5D-3L tariff to an unconscious health state. This assumption is in keeping with broader methodological practice for trial-based economic evaluations conducted in critical care settings [38]. Moreover, we recently demonstrated that applying alternative fixed baseline utility scores generally had no effect on incremental QALY calculations [38].…”
Section: Discussionsupporting
confidence: 52%
“…This assumption is in keeping with broader methodological practice for trial-based economic evaluations conducted in critical care settings [38]. Moreover, we recently demonstrated that applying alternative fixed baseline utility scores generally had no effect on incremental QALY calculations [38]. Second, approximately 35% of QALY data and 6-40% of costs (at the component level) were missing by 6 months.…”
Section: Discussionmentioning
confidence: 57%
“…This may be an unrealistic assumption, but it is in keeping with broader methodological practice for trial-based economic evaluations conducted in emergency and critical care settings. 56 Moreover, we have recently demonstrated that assuming an alternative fixed baseline utility score, for example a utility score of zero representing death, would have no effect on the area under the curve within the incremental QALY calculations. 56 Furthermore, the utility assessments performed around the point of hospital discharge required participants to reflect on their health state of at least 1 month earlier, and may, therefore, suffer from some recall bias.…”
Section: Discussionmentioning
confidence: 99%
“…56 Moreover, we have recently demonstrated that assuming an alternative fixed baseline utility score, for example a utility score of zero representing death, would have no effect on the area under the curve within the incremental QALY calculations. 56 Furthermore, the utility assessments performed around the point of hospital discharge required participants to reflect on their health state of at least 1 month earlier, and may, therefore, suffer from some recall bias. Consequently, the QALY values generated for the purposes of the baseline cost-effectiveness analysis were based on one fixed baseline time point and utility value.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline EQ-5D-5L values will be imputed to reflect the unconscious health state and applied to all patients, minimising potential bias in the QALY AUC calculation. 21,22 Within-trial analysis (to 12 months) using bivariate regression of costs and QALYs will inform a probabilistic assessment of the incremental cost-effectiveness ratio, 23 cost-effectiveness acceptability and value-ofinformation of further research. Following best practice, missingness mechanisms will be explored and multiple imputation methods will be used within the analysis.…”
Section: Economic Analysesmentioning
confidence: 99%